ANALYSIS OF INTEREST RATES AND FACTORS INFLUENCING THEM ON CREDIT AND DEPOSIT OPERATIONS OF COMMERCIAL BANKS - Orifova Dilnoza Obid Qizi (Galaxy International Interdisciplinary Research Journal, 2023)
Interest rates play a pivotal role in shaping the financial landscape, particularly in the credit and deposit operations of commercial banks. Understanding the dynamics of interest rates and the factors that influence them is crucial for both banks and individuals alike. This article aims to provide a comprehensive analysis of interest rates and the various factors that impact them in the context of credit and deposit operations of commercial banks. By exploring the relationship between interest rates and economic factors, monetary policy, market forces, and risk considerations, this article sheds light on the intricate workings of interest rates in the banking industry.